Application of sirolimus in an infant presenting with a life-threatening lymphatic malformation of the head and neck: a case report - Yu, Shuying; Guo, Xiaowen (Frontiers in Pediatrics, 2025)
Extensive lymphatic malformations in the head and neck region pose a significant risk due to potential airway compression, and conventional treatment modalities have proven largely ineffective. Currently, systemic administration of sirolimus is recognized as a promising therapeutic approach for complex lymphatic malformations. Nevertheless, the appropriate dosage, optimal blood concentration, efficacy, and safety profile of sirolimus in pediatric patients remain inadequately characterized. In this report, we present a clinical case involving a 3-month-old male infant diagnosed with tongue lymphatic malformation, treated with sirolimus. It is noteworthy that the trough concentration of sirolimus is influenced by both genetic and non-genetic factors, including physiological and pathological conditions, as well as drug-food and drug-drug interactions in pediatric patients. Despite the sirolimus concentration below the target range during treatment, a reduction in tumor size was observed. Additionally, based on the patient's medical history, adjustments in medication, and liver function assessments, the pharmacist has excluded the likelihood of sirolimus-induced hepatotoxicity. This case underscores the safety and efficacy of sirolimus in managing extensive lymphatic malformations of the head and neck in infants. Regular monitoring and analysis of variations in sirolimus blood concentrations, coupled with long-term follow-up observations, are essential for enhancing treatment efficacy and minimizing toxicity risks.